2013
DOI: 10.1039/c3ta00936j
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and visible-light photocatalysis of hollow rock-salt TiO1−xNx nanoparticles

Abstract: A simple method for the preparation of hollow rock-salt TiO 1Àx N x nanoparticles and their visible-light photocatalytic activities are presented. By thermal annealing of TiO 2 nanoparticles under NH 3 /N 2 gas flow at 800 C, a rock-salt TiO phase was achieved far below its transition temperature to a monoclinic TiO phase (1250 C). The composition of the nanoparticles was revealed to be Ti 0.7 (O 0.67 N 0.33 ) 1 by detailed structural and compositional characterizations, and their structural stability was crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Finally, we should note that in the case of the TiON–Ir the Ir geometric loading is approximately 150-fold smaller than in PEM electrolyzers with the best state-of-the-art performance . We note that loadings of such low range are not expected to be incorporated in the real OER anode just yet, but the TiON–Ir composite could pave the way for lowering Ir content …”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Finally, we should note that in the case of the TiON–Ir the Ir geometric loading is approximately 150-fold smaller than in PEM electrolyzers with the best state-of-the-art performance . We note that loadings of such low range are not expected to be incorporated in the real OER anode just yet, but the TiON–Ir composite could pave the way for lowering Ir content …”
Section: Resultsmentioning
confidence: 93%
“…16 We note that loadings of such low range are not expected to be incorporated in the real OER anode just yet, but the TiON−Ir composite could pave the way for lowering Ir content. 77…”
Section: Resultsmentioning
confidence: 99%
“…First, TiO contains more than 15% vacancies on both Ti and O sites depending on its stoichiometry, resulting in a rock salt structure with plenty of defects. 28 This suggests that the oxygen vacancy (O-vacancy) sites could serve as a good place for N atom incorporation. Second, the Ti 2+ species could donate electrons to incoming N atoms to render them stabilized in the form of N 3À .…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10] One of the most notable photocatalysts is TiO 2 , which however has limitations in visible light absorption. 11,12 BiOBr (bismuth oxybromide) as a relatively new member of the family of photocatalysts has been demonstrated to be a promising photocatalyst that has suitable band gap, can degrade a wide range of toxic organic pollutants and metal ions in water under visible light illumination, and shows good chemical stability and is eco-friendly. [13][14][15][16][17] Previous studies have revealed that the photocatalytic activity of BiOBr is determined by not only the surface atomic structure, but also the grain size, morphology and structure, and dominantly exposed facets.…”
Section: Introductionmentioning
confidence: 99%